Presence of Bartonella Species in Wild Carnivores of Northern Spain - Gerrikagoitia, Xeider (American Society for Microbiology, 2012)
The genus Bartonella was detected by PCR in 5.7% (12/212) of wild carnivores from Northern Spain. Based on hybridization and sequence analyses, Bartonella henselae was identified in a wildcat (Felis silvestris), Bartonella rochalimae in a red fox (Vulpes vulpes) and in a wolf (Canis lupus), and Bartonella sp. in badgers (Meles meles).